The mediating role of certification in the relationship between green purchasing intention and green purchasing behavior in forestry - Hasan Alkan; Gökhan Topaloğlu (Turkish Journal of Forestry, 2023)
This research was carried out to determine the mediating effect of certification in forestry on the relationship between green purchase intention and green purchasing behavior. Questionnaire technique was used to obtain the data. For this purpose, a survey was conducted with 319 consumers in Aydın. SPSS 22 and AMOS program were used to analyze the data. The methods used in the analysis are explanatory factor analysis, confirmatory factor analysis and mediation analysis. The fit values of the model obtained according to the research findings were SRMR; 0.0605 CFI; 0.851 NFI; 0.787 TLI; 0.827 PNFI; 0.679 PGFI; 0.689 and RMSEA; 0.0704. As a result, the fit values were within the acceptable range and the model was validated. Considering the findings, certification information in forestry appears as a distinctive element in the formation of green purchasing behavior of consumers. With the validation of the model, it was concluded that the certification variable was a partial mediator variable. Considering that the concept of green cannot be considered separately from certification studies in forestry, it is a remarkable finding in terms of forestry.